The Legal Tradition of the Ukrainian People as the Basis of State-Political System in the State-Building Ideals of Rostyslav Lashchenko - Turchyn, Yaryna; Ivasechko, Olga (Studia Warmińskie, 2018)
This article presents the views of Rostislav Laszczenko on the idea of building a Ukrainian state. Rostislav Laszczenko was a Ukrainian lawyer, a statesman from the time of the national liberation struggles of the Ukrainian nation for independence in 1917-1920. It was shown that, according to Laszczenko, the beginnings of Ukrainian statehood can be traced back to the times of Kievan Rus, because then certain legal traditions and norms began to function in Ukrainian society. According to Laszczenko, in the following centuries, these traditions and norms were then developed and finally resulted in the creation of the Ukrainian State in 1918, when General Pawlo Skoropadski, supported by the central states, made a political upheaval. As a result of this coup, the Ukrainian State was formally established and the process of creating state structures began. The newly formed state quickly collapsed, and its territory was absorbed by neighboring countries: Poland, Czechoslovakia, Romania and above all the USSR. The article indicates that according to R. Laszczenko, one of the reasons for the failure of the construction of a stable and stable Ukrainian State in 1917-1920 was the imperfection of its legal system.